Impact of manganese amino acid complex on tissue-specific trace mineral distribution and corpus luteum function in gilts. (12th May 2021) - Studer, Jamie M; Kiefer, Zoe E; Goetz, Brady M; Keating, Aileen F; Baumgard, Lance H; Rambo, Zachary J; Schweer, Wesley P; Wilson, Mark E; Rapp, Christof; Ross, Jason W
Abstract: Functional corpora lutea (CL ) are required for pregnancy establishment and gestational maintenance in swine, and CL function is susceptible to environmental influences. Manganese (Mn ) could be critical in regulating CL function since it is a component of the antioxidant enzyme Mn superoxide dismutase (MnSOD ) as well as enzymes involved in cholesterol and steroid hormone synthesis. We hypothesized that a more bioavailable dietary Mn source would increase Mn content in the CL thereby influencing luteal function during the mid-luteal phase of the estrous cycle. Postpubertal gilts ( n = 32) were assigned to one of four gestation diets. The control diet (CON ) met or exceeded National Research Council (2012) requirements and was formulated to contain 20 parts per million (ppm ) of added Mn in the form of Mn sulfate. Three additional diets included 20 (treatment [TRT ]1), 40 (TRT2), or 60 (TRT3) ppm of added Mn from a Mn–amino acid complex (Availa-Mn; Zinpro Corporation) instead of Mn sulfate. Dietary treatment began at estrus synchronization onset and continued through 12 days post estrus (dpe ) of the ensuing estrous cycle. Blood samples were collected at estrus onset, which was assigned as 0 dpe, as well as 4, 8, and 12 dpe. Gilts were euthanized and tissues were collected at 12 dpe. Serum progesterone (P 4 ) increased ( P < 0.01) from 0 to 12 dpe but was unaffected by dietary treatment ( P = 0.15) and there was no effect of the interaction between day and treatment ( P = 0.85). Luteal Mn content increased ( P ≤ 0.05) by 19%, 21%, and 24% in gilts fed TRT1, TRT2, and TRT3, respectively, compared to CON. Luteal P4 concentrations decreased ( P = 0.03) 25%, 26%, and 32% in gilts fed TRT1, TRT2, and TRT3, respectively, compared to CON. Relative to CON gilts, CL calcium content decreased ( P = 0.02) by 36%, 24%, and 34% for TRT1, TRT2, and TRT3 gilts, respectively. Collectively, these data support the hypothesis that feeding a more bioavailable Mn source increases Mn accumulation in CL tissue. If and how this influences CL function may be related to altered luteal P4 concentrations.